Membrane Reconstitution of Monoamine Oxidase Enzymes on Supported Lipid Bilayers - Wang, Liulin (Langmuir : the ACS journal of surfaces and colloids, 2018)
Monoamine oxidase A and B (MAO-A and B) are mitochondrial outer membrane enzymes that are implicated in a number of human diseases, and the pharmacological inhibition of these enzymes is a promising therapeutic strategy to alleviate disease symptoms. It has been suggested that optimal levels of enzymatic activity occur in the membrane-associated state, although details of the membrane association process remain to be understood. Herein, we have developed a supported lipid bilayer platform to study MAO-A and B binding and evaluate the effects of known pharmacological inhibitors on the membrane association process. By utilizing the quartz crystal microbalance-dissipation (QCM-D) technique, it was determined that both MAOs exhibit tight binding to negatively and positively charged bilayers with distinct concentration-dependent binding profiles while only transiently binding to neutral bilayers. Importantly, in the presence of known inhibitors, the MAOs showed increased binding to negatively charged bilayers, although there was no effect of inhibitor treatment on binding to positively charged bilayers. Taken together, our findings establish that the membrane association of MAOs is highly dependent on membrane surface charge, and we outline an experimental platform to support the in vitro reconstitution of monoamine oxidases on synthetic membranes, including the evaluation of pharmacological drug candidates